Perilaku Adaptasi Petani Tanaman Padi pada Perubahan Iklim di Desa Rantau Fajar Kecamatan Raman Utara - Damayanti, Nur Alfi Laila; Yanfika, Helvi; Rangga, Kordiyana K; Nikmatullah, Dewangga (Fakultas Pertanian, Universitas Lampung, 2022)
This study aims to find out the level of behavior of rice crop farmers and factors related to farmers' adaptation behavior to climate change in Rantau Fajar Village, North Raman Subdistrict, East Lampung Regency. The study was conducted in August-September 2021. The respondents numbered 84 farmers, who were obtained by random sampling. The study used survey methods with a quantitative descriptive approach, and was analyzed using spearman rank correlation tests. The results of this study show that the behavior of farmers' adaptation in the face of climate change is in a high category, which is seen based on the level of knowledge and attitudes of farmers who have understood climate conditions, although in the skills of farmers there is still a need for an increase in behavior. Factors related to farmers' adaptation behavior to climate change are: Long-Standing Farming, Farmer's Crowing Level, Extension Support, Government Support, and Farmer Group Support. Keywords: adaptation, behavior, climate change